2020
DOI: 10.22541/au.160218230.00714939/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of COVID-19 Pandemic on Anxiety Levels of Children with Cystic Fibrosis and Healthy Children

Abstract: Background Cystic fibrosis (CF) is a chronic disease causing recurrent respiratory tract infections. Viral respiratory tract infections are more severe in CF. The first case of COVID-19 was seen in Turkey on March 11, 2020 and nationwide school closure and lockdown were implemented. School closure and home confinement might have adverse effects on children's physical and mental health. In this study, we aimed to compare the effect of COVID-19 pandemic on psychological reactions of CF patients and healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Another study conducted in Turkey also found that the pandemic caused significant increase in anxiety amongst mothers of children with CF, as well as those with healthy children when compared to children with CF (13–18 years) 21 . Lower anxiety scores in children with CF compared to age‐matched healthy control group has also been reported elsewhere 20 . It was postulated that a potential reason for lower anxiety scores in children with CF may relate to previous exposure to stressful illness experiences, necessitating the early development of adaptive coping strategies when compared to a healthy control group who may be experiencing a serious health problem for the first time.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Another study conducted in Turkey also found that the pandemic caused significant increase in anxiety amongst mothers of children with CF, as well as those with healthy children when compared to children with CF (13–18 years) 21 . Lower anxiety scores in children with CF compared to age‐matched healthy control group has also been reported elsewhere 20 . It was postulated that a potential reason for lower anxiety scores in children with CF may relate to previous exposure to stressful illness experiences, necessitating the early development of adaptive coping strategies when compared to a healthy control group who may be experiencing a serious health problem for the first time.…”
Section: Discussionsupporting
confidence: 54%
“…A Belgian study assessed the impact of COVID-19 on emotional wellbeing of patients with CF (mean age 32.2 years) and parents of children with CF (mean age 39.4 years); reporting increased stress, fear and worry about CF and the future. 19 Two further studies have evaluated the impact of COVID-19 on anxiety in children with CF 20,21 and their mothers 21 reporting increased anxiety primarily amongst mothers of children with CF as well as those with non CF children compared to children with CF. 20,21 The UK government initially considered children and young adults with CF to be clinically extremely vulnerable to COVID-19 and recommended "shielding"-that is, to remain at home at all times and have no face to face contact with anyone outside of their household, except to attend to medical needs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations